Pachinko - Lee, Min Jin (New York : Grand Central Publishing, 2018)
"A new tour de force from the bestselling author of Free Food for Millionaires, for readers of The Kite Runner and Cutting for Stone. PACHINKO follows one Korean family through the generations, beginning in early 1900s Korea with Sunja, the prized daughter of a poor yet proud family, whose unplanned pregnancy threatens to shame them all. Deserted by her lover, Sunja is saved when a young tubercular minister offers to marry and bring her to Japan. So begins a sweeping saga of an exceptional family in exile from its homeland and caught in the indifferent arc of history. Through desperate struggles and hard-won triumphs, its members are bound together by deep roots as they face enduring questions of faith, family, and identity"--
Keywords: Families -- Korea -- Fiction; Domestic fiction